ANALISIS PERBANDINGAN ANTARA RASIO KEUANGAN DAN METODE ECONOMIC VALUE ADDED SEBAGAI PENGUKUR KINERJA KEUANGAN PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN ROKOK YANG TERDAFTAR DI BEI PERIODE TAHUN 2012 -2014 - Arisanti, Any; Bayangkara, IBK (Universitas 17 Agustus 1945 Surabaya, 2016)
This study aimed to describe and compare the company's financial performance as measured by the method of Economic Value Added (EVA) is a new approach which assesses the company's financial performance by taking into account the expectations of donors, particularly shareholders and creditors. Financial Ratios and analysis to assess the company's financial situation in the past, present and future. The research object is a cigarette company listed on the Stock Exchange in the period 2012 - 2014, that are PT. Gudang Garam Tbk, PT. HM Sampoerna Tbk, PT. Bentoel Internasional Investama Tbk, and PT. Wismilak Inti Makmur, Tbk. This type of research is comparative descriptive, while the data used is secondary data obtained from the Indonesia Stock Exchange. The Results of financial ratios calculation fluctuated every company each year. In the EVA calculation are the average of 2012 - 2014, PT. HM Sampoerna Tbk has the highest EVA value, then PT. Gudang Garam Tbk, hereinafter PT. Bentoel Internasional Investama Tbk and last PT. Wismilak Inti Makmur, Tbk. EVA is always positive (EVA> 0) in 2012-2014 means that the management company is able to create economic value for shareholders, and of course the company's financial performance is also good.Keywords: financial performance, financial ratios, EVA